Digital entrepreneurship competence of vocational students - Mahmudah, Fitri Nur; Baswedan, Aliyah Rasyid; Cahyono, Sulistio Mukti (Faculty of Engineering, Universitas Negeri Yogyakarta, 2023)
Digital-preneurship is one way of learning as a medium for students to develop themselves and improve competencies as needed by the world of work. The purpose of this study was to determine the digital-preneruship competence of Vocational High School students. The method used in this research is qualitative with a single-case study approach. Research setting in SMK which has the title of Center of Excellence. The participants involved are Vocational High School students. The data analysis procedure used the Five-Phased Cycle of compiling, disassembling, reassembling, interpreting, and concluding. Data analysis using the software Atlas.ti version 9. The results of this study indicate that students' digital-preneurship competencies are resilient, digital marketing, business management, and brand development. Each component finding has indicators.